1993
DOI: 10.1021/np50101a007
|View full text |Cite
|
Sign up to set email alerts
|

Triterpene Glycosides from the Roots of Dipsacus asper

Abstract: The roots of Dipsacus asper have yielded two new triterpenoid saponins, dipsacus saponins B [1] and C [2], which have been characterized by chemical and spectral means and spectral means as hederagenin-3-O-beta-D-glucopyranosyl-(1-->4)-[alpha-L-rhamnopy ran osyl- (1-->6)]-beta-D-glucopyranosyl-(1-->3)-alpha-L-rhamnopyranosyl-(1-->2)-a lpha- L-arabinopyranoside [1] and hederagenin-3-O-beta-D-xylopyranosyl-(1-->4)- beta-D-glucopyranosyl-(1-->4)-beta-D-glucopyranosyl-(1-->3)-[alpha-L- rhamnopyranosyl-(1-->4)]-alp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
27
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 3 publications
0
27
0
Order By: Relevance
“…In our screening for the anti-inflammatory activity of traditional medicinal plants, we found that a water extract of D. asper roots showed significantly inhibitory activity against the production of nitric oxide (NO) in lipopolysaccharide (LPS)-activated murine macrophage RAW264.7 cells with an IC 50 value of 45.1 µg/mL. Bioassay-guided fractionation led to the isolation of a new pyridine alkaloid-coupled iridoid glucoside, dipasperoside A (1), and 20 known compounds [vanillic acid (2), 14) 3,4-dihydroxybenzoic acid (3), 14) 3,4-dihydroxybenzaldehyde (4), 15) caffeic acid (5), 14) 3β,5α-tetrahydrodesoxycordifoline lactam (6), 16) 4,5-dicaffeoylquinic acid (7), 17) 3,5-dicaffeoylquinic acid (8), 17) 3,4-dicaffeoylquinic acid (9), 17) sweroside (10), 18) loganin (11), 18) cantleyoside (12), 19) dipsanoside A (13), 20) dipsanoside B (14), 20) triplostoside A (15), 19) akebia saponin D (16), 21) loganic acid (17), 19) sylvestroside I (18), 19) 4′-O-acetyl-akebia saponin D (19), 21) dipsacus saponin A (20), 22) and…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In our screening for the anti-inflammatory activity of traditional medicinal plants, we found that a water extract of D. asper roots showed significantly inhibitory activity against the production of nitric oxide (NO) in lipopolysaccharide (LPS)-activated murine macrophage RAW264.7 cells with an IC 50 value of 45.1 µg/mL. Bioassay-guided fractionation led to the isolation of a new pyridine alkaloid-coupled iridoid glucoside, dipasperoside A (1), and 20 known compounds [vanillic acid (2), 14) 3,4-dihydroxybenzoic acid (3), 14) 3,4-dihydroxybenzaldehyde (4), 15) caffeic acid (5), 14) 3β,5α-tetrahydrodesoxycordifoline lactam (6), 16) 4,5-dicaffeoylquinic acid (7), 17) 3,5-dicaffeoylquinic acid (8), 17) 3,4-dicaffeoylquinic acid (9), 17) sweroside (10), 18) loganin (11), 18) cantleyoside (12), 19) dipsanoside A (13), 20) dipsanoside B (14), 20) triplostoside A (15), 19) akebia saponin D (16), 21) loganic acid (17), 19) sylvestroside I (18), 19) 4′-O-acetyl-akebia saponin D (19), 21) dipsacus saponin A (20), 22) and…”
mentioning
confidence: 99%
“…18) indicated that the hydroxyl group at C-7 in both loganin moieties of 1 was esterified. The 22 carbon signals including those of the above mentioned groups and an ester carbonyl carbon (δ C 165.9, C-7″). These data were similar to those of lonijaposide A isolated from the flower buds of Lonicera japonica, 25) except for the absence of O-methyl and carboxypropyl groups, and a high-field shift of C-7″ (1: δ C 165.9; lonijaposide A: δ C 170.5).…”
mentioning
confidence: 99%
“…The roots of D. asper has been used in traditional Chinese medicine for hundreds of years as an antiosteoporosis, tonic and antiaging agent for the therapy of low back pain, traumatic hematoma, threatened abortion and bone fractures [9,10]. In the previous studies, dozens of chemical constituents, including triterpenoids, triterpene saponins, iridoids, iridoid glucosides, lignans, phenolics, and alkaloids, have been identified from the roots of D. asper [9][10][11][12][13][14][15]. However, a literature survey has shown that there is no report on chemical composition of essential oil of D. asper and larvicidal activity of D. asper essential oil against mosquitoes.…”
Section: Introductionmentioning
confidence: 99%
“…The roots of Dipsacus asper have been used as a tonic, an analgesic and anti-inflammatory agent in traditional Chinese medicine for the therapy of low back pain, knee pain, rheumatic arthritis, traumatic hematoma, threaten abortion, and bone fractures (Namba, 1993). Several chemical constituents, particularly dipsacus saponins, iridoid glycosides and sterols have been identified from the root of D. asper (Kouno et al, 1990;Jung et al, 1993;Hung et al, 2005). Recently, saponins isolated from the roots this plant have been demonstrated to possess anti-inflammatory, antinociceptive, and anticomplementary effects (Jung, 1995;Suh et al, 2000;Oh et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Several chemical constituents, particularly dipsacus saponins, iridoid glycosides and sterols have been identified from the root of D. asper (Kouno et al, 1990;Jung et al, 1993;Hung et al, 2005). Recently, saponins isolated from the roots this plant have been demonstrated to possess anti-inflammatory, antinociceptive, and anticomplementary effects (Jung, 1995;Suh et al, 2000;Oh et al, 1999). However, there are fewer reports specifically concerning D. asper.…”
Section: Introductionmentioning
confidence: 99%